Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1754-9493-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Iliofemoral deep vein thrombosis after tibial plateau fracture fixation related to undiagnosed May-Thurner syndrome: a case report

Abstract: BackgroundMay-Thurner Syndrome (MTS) represents an anatomic variation of the iliac vessels, in which the left common iliac vein is compressed by an overriding iliac artery. Patients with this abnormality are predisposed to the formation of a left-sided iliofemoral deep venous thrombosis (DVT). While DVT is a familiar complication in the setting of lower extremity trauma, there are no previous reports of MTS complicating the care of patients requiring orthopaedic surgery.Case presentationWe present the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…24,41,65 However, venography is typically not performed unless thrombolysis is anticipated, owing to its invasive nature and postprocedural complications (eg, phlebitis). 66 Besides venography, other imaging techniques, such as multidetector computed tomography (CT) scans, 15,41,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] magnetic resonance venography (MRV), 23,60,[84][85][86][87] and intravascular ultrasonography, 16,[88][89][90][91][92][93] have been used to image iliac venous compression and are described in Table 2.…”
Section: Iag Nos Is Of May-th Urner Syndromementioning
confidence: 99%
“…24,41,65 However, venography is typically not performed unless thrombolysis is anticipated, owing to its invasive nature and postprocedural complications (eg, phlebitis). 66 Besides venography, other imaging techniques, such as multidetector computed tomography (CT) scans, 15,41,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] magnetic resonance venography (MRV), 23,60,[84][85][86][87] and intravascular ultrasonography, 16,[88][89][90][91][92][93] have been used to image iliac venous compression and are described in Table 2.…”
Section: Iag Nos Is Of May-th Urner Syndromementioning
confidence: 99%
“…Surgery, pregnancy and prolonged rest have been described as acute trigger factors. 14 Based on autopsy findings, May & Thurner 1 reported a 22% prevalence of venous intraluminal "spurs" at the level at which the right common iliac artery crosses the left common iliac vein anteriorly. Since iliac vein thrombosis is more common on the left side, it is believed that the compression and the "spurs" described by May & Thurner are responsible for many of these cases.…”
Section: Epidemiologymentioning
confidence: 99%
“…Recently, some authors reported extensive left-sided DVT formation in orthopedic surgery patients with concomitant IVCS [6,7], but the exact influence of IVCS on DVT formation in hip fracture patients is not well established.…”
Section: Introductionmentioning
confidence: 99%